The Effect of Product Quality and Proce on Consumer Loyality with Consumer Satisfaction as an Intervening Variable (Case Study of Scarlett Bodi Lotion Consumers in Nias Raya University Student) - Sri Endang Putri Zagoto; Saidah Khairiyah Hasibuan; M Ardy Rafian; Dede Ruslan Asria Sapti; Raina Linda Sari (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThe purpose of this research is to investigate the effect of product quality and price on consumer loyalty, with consumer satisfaction serving as a moderator (case study of Scarlett body lotion users, Nias Raya, a university student). The method used in this study is path analysis. The results showed that based on the first structural equation, product quality and price have an effect on customer satisfaction both partially and combined. Based on the second structural equation, product quality, price and customer satisfaction significantly affect customer loyalty both partially and combined.